Superior efficacy of a human immunodeficiency virus vaccine combined with antiretroviral prevention in simian-human immunodeficiency virus-challenged nonhuman primates - Le,Grand R; Dereuddre-Bosquet,N; Dispinseri,S; Gosse,L; Desjardins,D; Shen,X; Tolazzi,M; Ochsenbauer,C; Saidi,H; Tomaras,G; Prague,M; Barnett,SW; et al. (Journal of Virology, 2016)
Although vaccines and antiretroviral (ARV) prevention have demonstrated partial success against human immunodeficiency virus (HIV) infection in clinical trials, their combined introduction could provide more potent protection. Furthermore, combination approaches could ameliorate the potential increased risk of infection following vaccination in the absence of protective immunity. We used a nonhuman primate model to determine potential interactions of combining a partially effective ARV microbicide with an envelope-based vaccine. The vaccine alone provided no protection from infection following 12 consecutive low-dose intravaginal challenges with simian-HIV strain SF162P3, with more animals infected compared to naive controls. The microbicide alone provided a 68% reduction in the risk of infection relative to that of the vaccine group and a 45% reduction relative to that of naive controls. The vaccine-microbicide combination provided an 88% reduction in the per-exposure risk of infection relative to the vaccine alone and a 79% reduction relative to that of the controls. Protected animals in the vaccine-microbicide group were challenged a further 12 times in the absence of microbicide and demonstrated a 98% reduction in the risk of infection. A total risk reduction of 91% was observed in this group over 24 exposures (P = 0.004). These important findings suggest that combined implementation of new biomedical prevention strategies may provide significant gains in HIV prevention.IMPORTANCE There is a pressing need to maximize the impact of new biomedical prevention tools in the face of the 2 million HIV infections that occur each year. Combined implementation of complementary biomedical approaches could create additive or synergistic effects that drive improved reduction of HIV incidence. Therefore, we assessed a combination of an untested vaccine with an ARV-based microbicide in a nonhuman primate vaginal challenge model. The vaccine alone provided no protection (and ma